Application of Dempster-Shafer Theory Method in Expert System for Diagnosis of Psychological Disorders in Children - Azhari, M. Faishal; Putri, Raissa Amanda (Brilliance: Research of Artificial Intelligence, 2024)
The development of technology at this time has changed very rapidly in recent decades. Expert system is one of the sub-sections of artificial intelligence that aims to process and display the results of the conclusion of the previous process based on the knowledge that has been obtained. The purpose of this research is to apply the Dempster-Shafer method to the expert system for diagnosing psychological disorders in children and to design and build an expert system using the Dempster-Shafer method on a website-based expert system for diagnosing psychological disorders in children. Based on the results and discussion in this study, it can be concluded that the Dempster Shafer Method can be applied properly in an expert system for diagnosing psychological disorders in children. The Dempster Shafer method in this system gets results that are accurate enough so that it can generate a diagnosis based on symptoms accompanied by a handling solution. This expert system application for diagnosing psychological disorders in children can diagnose and determine the diagnosis results from consultations conducted by users using the Dempster Shafer method. Where in the example case, the percentage result is around 87.15%. This system can also help parents to get information about children's psychological disorders, symptoms, and solutions that can be applied.